Therapeutic potential of the mitochondria-targeted antioxidant MitoQ in mitochondrial-ROS induced sensorineural hearing loss caused by Idh2 deficiency - Ye-Ri Kim; Jeong-In Baek; Sung Hwan Kim; Min-A Kim; Byeonghyeon Lee; Nari Ryu; Kyung-Hee Kim; Deok-Gyun Choi; Hye-Min Kim; Michael P. Murphy; Greg Macpherson; Yeon-Sik Choo; et al. (Redox Biology, 2019)
Mitochondrial NADP+-dependent isocitrate dehydrogenase 2 (IDH2) is a major NADPH-producing enzyme which is essential for maintaining the mitochondrial redox balance in cells. We sought to determine whether IDH2 deficiency induces mitochondrial dysfunction and modulates auditory function, and investigated the protective potential of an antioxidant agent against reactive oxygen species (ROS)-induced cochlear damage in Idh2 knockout (Idh2−/−) mice. Idh2 deficiency leads to damages to hair cells and spiral ganglion neurons (SGNs) in the cochlea and ultimately to apoptotic cell death and progressive sensorineural hearing loss in Idh2−/− mice. Loss of IDH2 activity led to decreased levels of NADPH and glutathione causing abnormal ROS accumulation and oxidative damage, which might trigger apoptosis signal in hair cells and SGNs in Idh2−/− mice. We performed ex vivo experiments to determine whether administration of mitochondria-targeted antioxidants might protect or induce recovery of cells from ROS-induced apoptosis in Idh2-deficient mouse cochlea. MitoQ almost completely neutralized the H2O2-induced ototoxicity, as the survival rate of Idh2−/− hair cells were restored to normal levels. In addition, the lack of IDH2 led to the accumulation of mitochondrial ROS and the depolarization of ΔΨm, resulting in hair cell loss. In the present study, we identified that IDH2 is indispensable for the functional maintenance and survival of hair cells and SGNs. Moreover, the hair cell degeneration caused by IDH2 deficiency can be prevented by MitoQ, which suggests that Idh2−/− mice could be a valuable animal model for evaluating the therapeutic effects of various antioxidant candidates to overcome ROS-induced hearing loss. Keywords: Idh2, NADP+, ROS, Hearing loss, Antioxidant, MitoQ